Global change on the roof of the world: Vulnerability of Himalayan otter species to land use and climate alterations. (20th July 2021) - Jamwal, Pushpinder S.; Di Febbraro, Mirko; Carranza, Maria Laura; Savage, Melissa; Loy, Anna
Abstract: Aim: Climate Change Vulnerability Assessment (CCVA) prescribes the quantification of species vulnerability based on three components: sensitivity, adaptive capacity and exposure. Such assessments should be performed through combined approaches that integrate trait‐based elements (e.g., measures of species sensitivity such as niche width) with correlative tools quantifying exposure (magnitude of changes in climate within species habitat). Furthermore, as land use alterations may increase climate impacts on biodiversity, CCVAs should focus on both climate and land use change effects. Unfortunately, most of such assessments have so far focused exclusively on exposure to climate change. Location: Himalaya. Methods: We evaluated the vulnerability of three otter species occurring in the Himalayan region, that is, Aonyx cinereus, Lutra lutra and Lutrogale perspicillata, to 2050 climate and land use change through the recently proposed Climate Niche Factor Analysis (CNFA) framework combined with Species Distribution Models. Results: Future climate and land use change will reduce (6%–15%) and shift (10%–18%) the geographical range of the three species in the Himalaya, with land use alterations exerting far more severe effects than climate change. Among vulnerability components, sensitivity played a greater role than exposure in determining the vulnerability of the otters. Specifically, the most specialist species, L. perspicillata, showed the highest vulnerability in comparison with the most generalist, L. lutra . Main conclusions: Our results underline how coupling climate and land use change components in CCVAs can generate diverging predictions of species vulnerability compared to approaches relying on climate change only. Moreover, intrinsic components, such as species sensitivity, proved significantly more important in determining vulnerability than extrinsic metrics such as habitat exposure.